Alcohol Use / Abuse in Medical Students - Sogi Uematzu, Cecilia (2001)
OBJECTIVE: To study the frequency of alcohol use/abuse, its distribution by gender and age and associated risk factors in undergraduate medical students. MATERIAL AND METHODS: A mental health survey data base from 1115 medical students on a public university of Lima City was used. RESULTS: The frequency of CAGE positive, indicator of drinking problem, was 13,7%. The alcohol consumption onset mean age was earlier in the younger students, especially in women. Multivariate analysis showed significant association of CAGE positive with the year of study, antisocial features and male sex. CONCLUSION: Although there were differences in the frequency of alcohol use/abuse by gender in favor of male, female students, mainly the younger women, are tending to meet the male alcohol drinking pattern. Key words: Alcoholism; Students, Medical; Social Problems.